Brand Awareness and Social Media Communication inFrozen Food Management - Amalia, Arina Fatma; Widjayanti, Arifiani; Wibowo, Eddy Kusponco (Inisiatif Masyarakat Jurnal Indonesia (IMAJI), 2025)
Instagram and WhatsApp have become popular communication tools for business management in various industries, including the frozen food sector. This study aims to determine the influence of social media marketing and brand awareness on the management of frozen food sales in South Tambun, Bekasi, West Java. This study took a quantitative approach, involving the distribution of questionnaires to 124 respondents. The data were analysed using multiple linear regression analysis. The results indicate that social media marketing has a significant and positive effect on purchasing decisions, as evidenced by the t-test (t-count: 7.928 > t-table: 1.979 and sig.: 0.000 < 0.05). Brand awareness (X²) was also found to significantly affect frozen food purchasing decisions, with an F-count of 165.832 > F-table of 3.07 and a sig. of 0.000 < 0.05. The coefficient of determination (R²) of the social media marketing and brand awareness variables on purchasing decisions was found to be 72.6%. The remaining 27.4% is explained by other causes outside the scope of the research variables.